Tarbawi Method As A Qur’anic Learning Strategy To Foster Qur’anic Character In Islamic Schools - Rachman, Abdur; Samsul Ulum, Mohammad; Yaqien, Nurul (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the implementation of the Tarbawi method as a Qur’anic learning strategy in fostering Qur’anic character among students at an Integrated Islamic Junior High School. The Tarbawi method is known for its flexibility and emphasis on tahsin, tahfidz, and adab cultivation through the TANDUR approach (Grow, Experience, Name, Demonstrate, Repeat, Celebrate). This research employs a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving tahfidz teachers, Takhasus class students, and instructional documents. Data analysis was conducted through reduction, presentation, and verification to obtain a comprehensive understanding. The findings reveal that the Tarbawi method effectively improves students’ recitation quality, memorization, and mastery of tajwid. Furthermore, its implementation significantly contributes to the development of religious character traits such as discipline, responsibility, perseverance, and love for the Qur’an. Challenges encountered include learning fatigue, similarities among verses, and limited time. Solutions applied include emotional support, the use of interactive media, and synergy with parents. In conclusion, the Tarbawi method serves not only as an effective Qur’anic learning strategy but also as a holistic instrument for nurturing Qur’anic character. This model is recommended for adoption in other Islamic educational institutions to produce generations with noble character and a Qur’anic worldview.